Study on the Effect of Aspirin Treatment to Improve the Growth of Maize Plants Exposed to Low Temperatures - Rabha Buhwish Hamad; Ahlam Abdalla Alaila (African Journal of Advanced Pure and Applied Sciences, 2026)
The purpose of the research to assess how aspirin solution affected Zea mays L. plants’ ability to withstand low temperatures. This study examined how aspirin solution affected the total carbohydrate content, photosynthetic pigments, and a few growth indices of Zea mays L plants under cold stress. Three alternative planting dates were used for cultivation. The first planting date was July 22, 2024, with a temperature of 30 ± 2 °C. November 22, 2024, was the second planting date, and the temperature was 15 ± 2 °C. At a temperature of 10C0 ± 2C0, the third planting date was January 22, 2025. Irrigation took place every other day during the 21-day cultivation period. Each group was split into two halves, one of which was irrigated with 100 milliliters of distilled water and the other with 100 milliliters of a 0.5 mM of aspirin solution. Plants were taken after 21 days, and measurements were made of fresh and dry biomass, photosynthetic pigments, carbohydrate, root length and shoot height. This study suggested that maize plants are susceptible to cold by showing decreased growth metrics at low temperatures. The findings of the research demonstrated that cold-stressed maize plants grew better following treatment, showing that aspirin solution administration increased the plants’ resistance to chilly weather.